An Evaluation of the Feedback Loops in the Poverty Focus of World Bank Operations - Fardoust, Shahrokh; Kanbur, Ravi; Luo, Xubei; Sundberg, Mark (Elsevier, 2018)
The World Bank Group in 2013 made the elimination of extreme poverty by 2030 a central institutional focus and purpose. This paper, based on an evaluation conducted by the Independent Evaluation Group of the World Bank Group, examines how, and how well, the Bank uses feedback loops to enhance the poverty focus of its operations. Feedback loops are important for every element of the results chain running from data, to diagnostics, to strategy formulation and finally to strategy implementation. The evaluation uses a range of instruments, including surveys of stakeholders and World Bank staff, focus group meetings, country case studies and systematic reviews of Bank lending and non-lending operations. We find that while the Bank generates useful information on poverty reduction from its projects and programs, the feedback loops – from outcomes to data analysis to diagnostics to strategy formulation and implementation – have generally been weak, with sizable variation across countries.